2016
DOI: 10.1002/ps.4310
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of insecticide efficacy and resistance inDrosophila suzukii(Matsumura) (Diptera: Drosophilidae) populations from British Columbia, Canada

Abstract: Possible reasons reported in D. melanogaster studies where resistance did not occur after insecticide selection included avoidance and associated microbial complexes. The low level of malathion resistance observed in the selected SWD populations and a field-collected population is useful information in the development of insecticide resistance management programmes. © 2016 Her Majesty the Queen in Right of Canada Pest Management Science © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 44 publications
5
56
3
Order By: Relevance
“…Longer‐term D. suzukii data generated in this study (not shown), resulted in mortality levels similar to those found in studies conducted previously. Generally, in earlier studies, adult mortality rates for malathion, spinetoram, zeta‐cypermethrin, and methomyl were similar to those found in the current study and these insecticides are effective at managing this insect . The current study, however, provides more detailed insight into rapid toxic effects of different insecticides.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Longer‐term D. suzukii data generated in this study (not shown), resulted in mortality levels similar to those found in studies conducted previously. Generally, in earlier studies, adult mortality rates for malathion, spinetoram, zeta‐cypermethrin, and methomyl were similar to those found in the current study and these insecticides are effective at managing this insect . The current study, however, provides more detailed insight into rapid toxic effects of different insecticides.…”
Section: Discussionsupporting
confidence: 84%
“…did not provide information of the effects of different spray technologies and insecticides on crop infestation levels. Earlier studies of D. suzukii insecticide mortality were relatively consistent compared with the data generated here, with zeta‐cypermethrin being the most effective of the tested compounds . Mortality rates reported by Van Timmeren et al .…”
Section: Discussionsupporting
confidence: 57%
“…Insecticides with some effectiveness against D. suzukii include organophosphates, pyrethrins and spinosyns; at present, an effective insecticide class for suppression of D. suzukii is perceived to be spinosyns (spinosad and spinetoram) while the neonicotinoid insecticides tend to be less effective against adults [26,27,28,29]. The narrow range of options, particularly in organic production, requires that insecticide treatments are carefully optimized in order to prolong their effectiveness and counter the development of resistance [29,30]. Frequent, prophylactic, and sometimes superfluous insecticide applications add to the growers’ private costs and also have negative external effects due to detrimental impacts on the environment and human health [31].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Asobara, Ganaspis, invasive species, Leptopilina, pre-oviposition period, spotted wing drosophila short development time of the fly, they have to be applied regularly and can cause severe environmental and health concerns (Bruck et al, 2011;Cuthbertson, Collins, Blackburn, Audsley, & Bell, 2014;Sampson, Werle, Stringer, & Adamczyk, 2017;Smirle, Zurowski, Ayyanath, Scott, & MacKenzie, 2017;Van Timmeren & Isaacs, 2013).…”
Section: Introductionmentioning
confidence: 99%